Analisis Pengetahuan, Pemahaman, dan Penerapan Guru Matematika Tingkat SMP Sederajat Tentang Etnomatematika Dalam Praktik Kegiatan Pembelajaran Matematika - Adinda Dewi Gita; Farradina Latif; Melinda Dwi Agustina; Nabillah Pangesti Rahayu (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
The aim of this research is to provide the application of ethnomathematics learning to teachers who do not yet understand ethnomathematics. This research also provides education to teachers that ethnomathematics methods can be used in mathematics material and in classroom learning. So that the nation's next generation will also be more familiar with the culture in Indonesia, because Indonesian culture is now rarely known to the younger generation who have been mixed with foreign cultures. This research is a descriptive type with a qualitative approach. The research design used is a preliminary study. The purpose of using a qualitative approach in this research is to determine the knowledge, understanding and application of mathematics teachers at junior high school level regarding ethnomathematics in the practice of mathematics learning activities. In terms of students' problems in learning mathematics, teachers must have knowledge and understanding of ethnomathematics, so that they can better master it. innovative and creative learning. Before implementing mathematics learning, the first start must start with the teacher first, because the teacher is the student's facilitator in learning. Ethnomathematics and academic mathematics have differences, but ethnomathematics can be used to help students in learning academic mathematics so that students can better understand and comprehend the learning taught by Teacher. Ethnomathematics has also been proven to improve learning outcomes, which has been proven by the research studies mentioned above. Therefore, ethnomathematics can be used by teachers to carry out effective and enjoyable learning and can increase students' love of understanding their own culture.